2019
DOI: 10.1016/j.ccell.2019.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomics in Medulloblastoma Reveals Tumor-Initiating Progenitors and Oncogenic Cascades during Tumorigenesis and Relapse

Abstract: Highlights d Single-cell-omics reveal OLIG2 + glial progenitors as tumorinitiating cells in MB d OLIG2 + cells are quiescent stem-like in full-blown MB but reemerge during relapse d Ablation of mitotic OLIG2 + cells or deletion of Olig2 impedes MB tumor initiation d OLIG2 activates HIPPO-YAP and AURORA-A/MYCN oncogenic networks to promote MB growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 73 publications
6
98
0
Order By: Relevance
“…Actually, rescue from hypoxia has been described to require the expression of olig2, essential for functional myelination [69]. It is thus plausible to assume that the characteristic expression of olig2 by stem cell like progenitors giving rise to MB [70] is related to the consequences of this vicious cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, rescue from hypoxia has been described to require the expression of olig2, essential for functional myelination [69]. It is thus plausible to assume that the characteristic expression of olig2 by stem cell like progenitors giving rise to MB [70] is related to the consequences of this vicious cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Although MBs are thought to originate from primitive and undeveloped cells in the brain, the cell of origin for MB subgroups remains controversial. Most recently, three single-cell RNA sequencing (scRNA-seq) studies have provided a clearer picture of MB putative subtype-specific origins, highlighting the molecular and cellular diversity of MB across all subgroups, with the potential insights into understanding of tumor development and treatment response [17][18][19].…”
Section: Cell Of Origins In Mb Subgroupsmentioning
confidence: 99%
“…Furthermore, genetically engineered mouse model studies demonstrated that SHH MBs arise from cerebellar granule neuron progenitors (GNPs) [62,63]. By single-cell transcriptomics of SHH mouse models, OLIG2 + glial lineage progenitors were identified to play a pivotal role in tumor initiation, therapy-resistance and recurrence [19]. Interestingly, SHH MBs in infants (≤3 years old) and adults (≥16 years old) are thought to originate from different GNP populations.…”
Section: Cell Of Origins In Mb Subgroupsmentioning
confidence: 99%
See 1 more Smart Citation
“…In glioblastoma, OLIG2 and RUNX2 TFs (among many other TFs) have been shown to robustly segregate two distinct cell states that have differential response to drug therapy; and suggest that these cells may contribute uniquely to therapeutic resistance [16]. Furthermore, OLIG2 has been shown to mark tumour propagating cells in both glioma and medulloblastoma, and associated with tumorigenesis and relapse [36,44]. In another instance, coordinated activity of core TFs: POU3F2, SOX2, SALL2 and OLIG2 are capable of reprogramming differentiated glioblastoma cells and restoring their tumourigenic capacity [45].…”
Section: Reverse‐engineering Enhancers To Characterize Transcription mentioning
confidence: 99%